Pulsatilla decoction suppresses matrix metalloproteinase-7-mediated leukocyte recruitment in dextran sulfate sodium-induced colitis mouse model - Lin, Ming-Kuem; Yang, Ya-Ting; Lin, Li-Jen; Yu, Wei-Hsuan; Chen, Huan-Yuan (BMC complementary and alternative medicine, 2022)
Background Intestinal inflammation is considered to be an important characteristic of ulcerative colitis (UC) and the current medical treatments for UC are usually proposed to suppress abnormal intestinal immune responses. Pulsatilla decoction (PD), a traditional Chinese medicine, is frequently used in UC treatments in Asian countries; however, the mechanism of the action of PD remains unclear. In the present study, the mechanism of the action of PD was elucidated in the dextran sulfate sodium (DSS)-induced colitis mouse model, a model to mimic UC. Methods Murine colitis was evaluated by comparing the disease activity index score. The intestinal inflammation was examined by histology analyses. The leukocyte infiltration in the colonic tissues was examined by immunohistochemistry analyses. The cytokines level in colonic tissues was examined by Multi-Plex immunoassay. The epithelial proliferation was evaluated by histological analyses. Immunofluorescence double staining was used to examine the expression of MMP-7 in the immune cells. Results In the DSS-induced colitis mouse model, administration of PD attenuated the intestinal inflammation, with a marked decrease in colonic infiltration of innate immune cells. Immunohistochemical analyses further showed that matrix metalloproteinase-7 (MMP-7) expressed by the infiltrating leukocytes, including neutrophils and macrophages was inhibited by PD treatment. PD increases the cytokine level of IL-6 in colonic tissues. Conclusion PD suppresses intestinal inflammation, with a marked decrease in colonic infiltration of innate immune cells, through decreasing MMP-7 expression. Keywords: Pulsatilla decoction, Intestinal inflammation, Leukocyte recruitment, Matrix metalloproteinase-7, Ulcerative colitis